Penggunaan Framework CodeIgniter pada Pengembangan Sistem Informasi Akuntansi Penggajian untuk Stasiun Pengisian Bulk Elpiji - Fitri Asih; Endang Haryani (Labkat Press KA FTIK UNIKOM, 2022)
Each company has workers who are authorized to receive compensation in the form of salary or wages in accordance with the agreement between the workers and the company. Proper payroll management will produce good quality payroll data and information. Currently payroll of SPBE PT. XYZ is manually managed by using spreadsheet application. Then, several problems arise, includes incorrect data input, time to process data into payroll reports is relatively long, which result in delays to disburse salaries to employees. Therefore, this study aims to analyze and develop a payroll accounting information system at SPBE PT. XYZ Salatiga. The basis used is the Codeigniter framework and the method is Waterfall. The result shows that the Payroll Accounting Information System at SPBE PT. XYZ Salatiga has been analyzed based on the on-going payroll procedure, then developed to overcome the weaknesses of the payroll process. The company's payroll management problems aforementioned can be overcome with this information system. This system is capable of managing employee data and position data; managing salary both additional and deduction factors; processing salary calculations to produce a salary register for a certain period; generating earning statement; as well as managing payroll supporting documents. This shows that the company's need for a Payroll Accounting Information System and internal control for payroll data accuracy can be fulfilled. In order to achieve this goal, the Payroll Accounting Information System is proposed to SPBE PT. XYZ Salatiga to be applied.